2014
DOI: 10.1016/j.fct.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of ochratoxin A induce micronucleus formation and delay DNA repair in human lymphocytes

Abstract: The contamination of food commodities by fungal toxins has attracted great interest because many of these mycotoxins are responsible for different diseases, including cancer and other chronic illnesses. Ochratoxin A (OTA) is a mycotoxin naturally present in food, and long-term exposure to food contaminated with low levels of OTA has been associated with renal cancer. In the present study, the cytotoxicity, cytostaticity, and genotoxicity of OTA (0.075-15 µM) in human lymphocytes were evaluated. A comet assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…Reported in vitro toxic effects of OTA include inhibition of cellular proliferation, apoptosis and impairment of barrier function and increasing membrane permeability (McLaughlin et al, 2004). OTA has been found to induce oxidative damage in vitro (Schaaf et al, 2002;Kamp et al, 2005;Mally et al, 2005) and in vivo (Petrik et al, 2003;Hsuuw et al, 2013) and to be genotoxic (Lebrun and Föllmann, 2002;González-Arias et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Reported in vitro toxic effects of OTA include inhibition of cellular proliferation, apoptosis and impairment of barrier function and increasing membrane permeability (McLaughlin et al, 2004). OTA has been found to induce oxidative damage in vitro (Schaaf et al, 2002;Kamp et al, 2005;Mally et al, 2005) and in vivo (Petrik et al, 2003;Hsuuw et al, 2013) and to be genotoxic (Lebrun and Föllmann, 2002;González-Arias et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, Pfohl-Leszkowicz et al (2012) have demonstrated the formation of OTA-derived DNA adducts and mutations and the involvement of the CYP450 enzymes in the bioactivation of OTA. The presence of DNA double-strand breaks and the micronucleus formation observed in in vivo or in vitro assays with cells capable of expressing cytochrome P450 (CYP450) enzymes support the OTA genotoxicity (González-Arias et al, 2014;Groene et al, 1996;Hibi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of OTA in feed has been linked to the development of nephrotoxicity, which, in rats, has been associated with renal adenomas and kidney tumours (Boorman, 1989;IARC, 1993). Several mechanisms of OTA toxicity have been described, including competition with phenylalanine for protein synthesis, inhibition of mitochondrial ATP production, production of free radicals, promotion of lipid peroxidation, and direct and indirect damage to DNA (El Khoury and Atoui, 2010;González-Arias et al, 2014;Ringot et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…44,47,48 1993 IARC raporunda, OTA ile ilgili genotoksisite verilerinde negatif sonuçlara yer verilse de mevcut birçok çalışmada, OTA'nın insan hücrele-rinde, fare ve sıçan gibi diğer memeli hücrelerinde DNA hasarına, mikroçekirdek ve DNA katım ürünü oluşumuna yol açarak genotoksik etki gös-terebileceği bildirilmiştir. 13,47,[49][50][51][52][53] OTA'nın temel toksik etki mekanizması, fenilalanine yapısal benzerliğinden dolayı, fenilanini substrat olarak kullanan birçok enzimi, özellikle fenilalanin-tRNA sentetazı inhibe ederek protein, DNA ve RNA sentezini inhibe etmesidir. 54 Ayrıca, ROT üretimini artırması ve lipit peroksidasyonunu artırarak hücre membranında hasar oluşturması da karsinojenik etkisi altında yatan diğer mekanizmalardır.…”
Section: Okratoksi̇nlerunclassified